White matter alterations in patients with MRI‐negative temporal lobe epilepsy and their asymptomatic siblings. (7th August 2015) - Whelan, Christopher D.; Alhusaini, Saud; O'Hanlon, Erik; Cheung, Maria; Iyer, Parames M.; Meaney, James F.; Fagan, Andrew J.; Boyle, Gerard; Delanty, Norman; Doherty, Colin P.; Cavalleri, Gianpiero L.
Summary Objective The identification of "endophenotypes"—measurable variations along the pathways between genes and distal disease state—may help deconstruct focal epilepsies into more sensitive phenomena and improve future efforts to map the genetic underpinnings of the disorder. In this study, we set out to determine if diffusion tensor imaging (DTI)–inferred white matter (WM) alterations represent a suitable structural endophenotype for focal epilepsy. Methods We recruited 25 patients with sporadic mesial temporal lobe epilepsy (MTLE) with normal magnetic resonance imaging (MRI) findings, 25 of their gender‐matched, asymptomatic siblings, and 60 control subjects. Whole‐brain, voxelwise statistics were conducted to identify regions of microstructural degeneration in patients with MTLE and/or their asymptomatic siblings. WM tracts exhibiting evidence of microstructural disruption were then reconstructed using deterministic tractography. Diffusion metrics including fractional anisotropy (FA) and mean diffusivity (MD) were compared across groups using a series of one‐way multivariate analyses of covariance (MANCOVAs). Results Voxelwise statistics revealed significant FA reductions in the corpus callosum (CC), bilateral superior longitudinal fasciculi (SLF), bilateral inferior longitudinal fasciculi (ILF), and left corticospinal tract (CST) in MTLE patients only. MD increases were observed in MTLE patients and their asymptomatic siblings in the left SLF and left CST. Deterministic tractography supported the voxelwise results, revealing significant FA alterations in the left SLF and CST in patients only and significant MD alterations in MTLE patients and their unaffected siblings. The diffusion scalars of MTLE patients and their asymptomatic siblings were highly correlated in the SLF and CST ipsilateral to patients' sides of seizure onset. Significance These findings confirm the presence of microstructural WM alterations in patients with MRI‐negative MTLE and provide preliminary support for a diffusion‐based endophenotype in the disorder. Further studies of narrow‐sense heritability in larger cohorts of first‐degree relatives of MTLE patients are required to confirm these results.